Magnetic resonance microscopy may enable distinction between normal histomorphological features and prostate cancer in the resected prostate gland. (1st June 2016) - Durand, Matthieu; Jain, Manu; Robinson, Brian; Aronowitz, Eric; El Douahy, Youssef; Leung, Robert; Scherr, Douglas S.; Ng, Amelia; Donzeau, Dominique; Amiel, Jean; Spincemaille, Pascal; Villers, Arnauld; et al.
Abstract : Objectives: To determine imaging protocol parameters for characterization of prostate tissue at histological length scales. Material and Methods: Rapid acquisition with relaxation enhancement, spin echo and gradient echo fast low angle shot data were acquired using ex vivo 3‐Tesla or 7‐Tesla magnetic field strengths from fresh prostatectomy specimens ( n = 15) obtained from either organ donor or patients with prostate cancer (PCa). To achieve the closest correspondence between histopathological components and magnetic resonance imaging (MRI) results, in terms of resolution and sectioning planes, multiple high‐resolution imaging protocols (ranging from a few minutes to overnight) were tested. Ductograms were generated as part of image post‐processing. Specimens were subsequently submitted for histopathological evaluation. Results: A total of seven imaging protocols were tested. Ex vivo 7‐Tesla MRI identified normal components of prostate glands, including ducts, blood vessels, concretions and stroma at a spatial resolution of 60 × 60 × 60 μm 3 to 107 × 107 × 500 μm 3 . Malignant glands and nests of tumour cells identified at 60 × 60 × 90 μm 3 were highly similar to low‐magnification (×2) histopathology. Ductograms enhanced the differentiation between benign and malignant glands. The results of the present study were encouraging, and further work is warranted with a larger sample size. Conclusion: We showed that critical histopathological features of the prostate gland can be identified with high‐resolution ex vivo MRI examination and this offers promise that MRI microscopy of PCa will ultimately be possible in vivo .